2016
DOI: 10.4049/jimmunol.1501345
|View full text |Cite
|
Sign up to set email alerts
|

GAPDH Binding to TNF-α mRNA Contributes to Posttranscriptional Repression in Monocytes: A Novel Mechanism of Communication between Inflammation and Metabolism

Abstract: Expression of the inflammatory cytokine TNF is tightly controlled. During endotoxin tolerance, transcription of TNF mRNA is repressed, although not entirely eliminated. Production of TNF cytokine, however, is further controlled by post-transcriptional regulation. In this study, we detail a mechanism of post-transcriptional repression of TNF mRNA by GAPDH binding to the TNF 3’UTR. Using RNA immunoprecipitation, we demonstrate that GAPDH-TNF mRNA binding increases when THP-1 monocytes are in a low glycolysis sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 60 publications
(60 reference statements)
7
97
0
2
Order By: Relevance
“…[161][162][163] Another key role of GAPDH involves binding to AU-rich elements in TNFα as well as IFNγ mRNA transcripts. 164,165 In the case of TNF, GAPDH binds to the 3′ untranslated region of TNF mRNA, leading to post-transcriptional repression in galactose-fed monocytes with limited availability of glucose and hence reduced rate of glycolysis. This repression of TNF translation can be reversed by increasing glycolysis at which time GAPDH binding to mRNA is lowered, thereby providing a means of fine-tuning the inflammatory response.…”
Section: Pkm2mentioning
confidence: 99%
“…[161][162][163] Another key role of GAPDH involves binding to AU-rich elements in TNFα as well as IFNγ mRNA transcripts. 164,165 In the case of TNF, GAPDH binds to the 3′ untranslated region of TNF mRNA, leading to post-transcriptional repression in galactose-fed monocytes with limited availability of glucose and hence reduced rate of glycolysis. This repression of TNF translation can be reversed by increasing glycolysis at which time GAPDH binding to mRNA is lowered, thereby providing a means of fine-tuning the inflammatory response.…”
Section: Pkm2mentioning
confidence: 99%
“…Similarly, Jiang and colleagues (2016) reported that the rate‐limiting glycolytic enzyme, 6‐phosphofructo‐2‐kinase/fructose‐2,6‐biphosphates 3 (PFKFB3) promotes the anti‐viral response of macrophages . Another crucial glycolytic enzyme, glyceraldehyde 3‐phosphate dehydrogenase (GAPDH) has been shown to post‐transcriptionally regulate TNFα expression in human monocytes and macrophages . They demonstrated that a low glycolysis state in THP1 monocytes promotes GAPDH‐TNFα mRNA binding leading to TNFα repression and conversely, during high glycolysis there is little GAPDH‐TNFα mRNA binding, leaving most of the TNFα mRNA to be translated .…”
Section: Metabolic Regulation Of Macrophage Polarizationmentioning
confidence: 99%
“…31 They demonstrated that a low glycolysis state in THP1 monocytes promotes GAPDH-TNFα mRNA binding leading to TNFα repression and conversely, during high glycolysis there is little GAPDH-TNFα mRNA binding, leaving most of the TNFα mRNA to be translated. 31 Stimulation of macrophages with TLR agonist also regulates the pentose phosphate pathway (PPP) by repressing its inhibitor, carbohydrate kinaselike protein (CARKL). 32 The PPP is a branch of the glycolytic pathway that results in the generation of NADPH and ribose-5-phosphate, required for nucleotide biosynthesis.…”
Section: Cd163 Cd163mentioning
confidence: 99%
“…The involvement of glycolysis on TNF‐α secretion by human LPS‐stimulated monocytes has been reported . In addition, Millet P et al recently demonstrated the specific binding of GAPDH on TNF‐α mRNA in THP‐1 monocytes, resulting in the posttranscriptional repression of TNF‐α mRNA . Interestingly, GAPDH and NADH significantly enhanced the production of IL‐10, which corresponded to the suppression of TNF‐α production (Figs.…”
Section: Discussionmentioning
confidence: 84%